Intervensi Psiko Edukasi terhadap Peningkatan Kesejahteraan Pasien Kanker: Systematic Review: Psycho-Educational Intervention to Improve Well-Being Cancer Patients: Systematic Review - Priyanto, Priyanto (Journal of Holistics and Health Sciences, 2024)
Medical-surgical nursing constitutes a pivotal aspect of the endeavour to optimise the well-being of cancer patients within the hospital setting. A variety of nursing interventions can facilitate the well-being of cancer patients, including those that provide psychoeducational support. The aim of this research is to synthesise the findings of studies examining the efficacy of psycho-educational interventions in enhancing the well-being of cancer patients. A systematic review was conducted in accordance with the PRISMA model, employing quantitative methods. The dependent variable is patient well-being, while psychoeducation is the independent variable. Of the 475 articles initially identified, seven articles published between 2013 and 2023 met the pre-established inclusion and exclusion criteria and were thus included in the review. The articles were sourced from four databases: The databases EBSCOhost, ProQuest, ScienceDirect, and Google Scholar were employed for the search. The evidence base demonstrates that psychoeducation can enhance physical, emotional, and mental well-being, facilitate sleep, promote relaxation, reduce stress, and alleviate muscle tension. Psychoeducation has been shown to overcome fatigue and lack of energy, depression and anxiety, improve mood, facilitate relaxation, and address nausea and other disorders. Psychoeducation has been proven to improve the patient's physical, psychological, and spiritual well-being. Psychoeducational therapy can be applied to cancer patients in hospital nursing services. ABSTRAK Asuhan keperawatan medikal bedah merupakan pelayanan penting untuk meningkatkan kesejahteraan pasien kanker di rumah sakit. Kesejahteraan pasien kanker dapat ditingkatkan melalui berbagai intervensi keperawatan, termasuk intervensi psiko edukasi. Tujuan penelitian ini untuk mensintesis kajian intervensi psiko edukasi terhadap peningkatan kesejahteraan pasien kanker. Tinjauan sistematis dilakukan dengan metode kuantitatif menggunakan model PRISMA. Variabel dependen adalah kesejahteraan pasien dan psiko edukasi sebagai variabel independen. Dari 475 artikel terseleksi ada tujuh artikel periode 2013-2023, yang memenuhi kriteria inklusi dan eksklusi yang dipilih. Artikel-artikel tersebut dikumpulkan dari empat sumber basis data yaitu: EBSCO host, proQuest, Science Direct dan Google Scholar. Psiko edukasi dapat meningkatkan kesejahteraan fisik, emosional dan mental, peningkatan tidur, relaksasi, menghilangkan stres dan meredakan ketegangan otot. Psiko edukasi dapat mengatasi kelelahan dan defisit energi, depresi dan kecemasan, memperbaik suasana hati, rileks, mual dan gangguan lainnya. Psiko edukasi terbukti mampu meningkatkan kesejahteraan fisik, psikis maupun spiritual pasien. Terapi psiko edukasi dapat diterapkan pada pasien kanker dalam pelayanan keperawatan di rumah sakit.